ERP Systems in Conditions of Digital Transformation of Business - Ivanović, Teodora; Marić, Mirjana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Nowadays there is an opportunity to see so much different technology that affects digital transformation. The way of doing business that was known until a few years ago is changing rapidly. The reason for this change is technology such as the Internet of things, Blockchain, Big data, Artificial intelligence, and Cloud technology. In this paper, the authors will outline the advantages and disadvantages of each of the above mentioned technologies, as well as give examples that will better illustrate the change that are happening in companies and their way of doing business in the domain of ERP systems. A particular focus of this paper will be on Cloud technology. The implementation of the Cloud ERP system in business necessarily leads to digital transformation. The authors will explore the positive effects of Cloud ERP system on business as well as the disadvantages of why some companies do not want to switch to this technology. The paper conducted empirical research using survey methods. Interviewing is conducted with 25 small-companies in Serbia. The obtained results will be presented in the form of drivers and barriers for the Cloud ERP technology in conditions of the digital transformation of business.